Lamnatibia, a new genus of the Polysphincta group of genera from Colombia (Hymenoptera: Ichneumonidae; Pimplinae) - Palacio, Edgard; Sääksjärvi, Ilari E.; Vahtera, Varpu (Zootaxa, 2007)
A new genus and species of the Polysphincta group of genera (Hymenoptera: Ichneumonidae; Pimplinae), Lamnatibia andina Palacio & Sääksjärvi, is described from the cloudforests of the Colombian Andes. The new genus can be easily separated from other genera of the Polysphincta group by the specialized shape of the fore and middle femora, the presence of a thin, longitudinal ridge in the inner face of the fore and middle tibiae, and the combined absence of occipital and epicnemial carinae. The new genus’s potential affinities with other genera of the Polysphincta group and its distribution are discussed.